SAINS ITU MENYENANGKAN: ASISTENSI MENGAJAR IPA PADA SMP DI KECAMATAN LEIHITU - Mahulette, Ferymon; Hajan, Esmi; Irwina, Irwina (Universitas Pattimura, 2023)
Science learning is still difficult to understand for Junior High School students in Leihitu District, Ambon Island. The main cause are the teacher's lack of creativity to designing concrete science lessons and incomplete laboratory facilities. This problem was slightly resolved with practical-based learning in the Lecturer Teaching Assistance of Pattimura University in 2022. The activity was carried out 4 times in class IX students at SMPN 103 Central Maluku and SMP Muhammadyah Mamala on December 13-17 2022. The topic being taught was electricity static and dynamic in life, magnetism and its uses, biotechnology and land and the sustainability of life. The mean scores of the two schools' student satisfaction levels for this activity were 3,401 and 3,408, respectively, in the strongly agree category. The continuation of Lecturer Teaching Assistance needs to be carried out because it is very beneficial to improve the quality of science learning in schools